2020
DOI: 10.1371/journal.pone.0234038
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of P2RX7 ameliorates liver injury by reducing inflammation and fibrosis

Abstract: Extracellular adenosine triphosphate (eATP) released by damaged cells, and its purinergic receptors, comprise a crucial signaling network after injury. Purinergic receptor P2X7 (P2RX7), a major driver of NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activation and IL-1β processing, has been shown to play a role in liver injury in murine diet-and chemically-induced liver injury models. It is unclear, however, whether P2RX7 plays a role in non-alcoholic steatohepatitis (NASH) and which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 80 publications
1
25
1
Order By: Relevance
“…In the present study, we confirm that the P2X7R stimulates collagen I secretion in vitro (Figure 3c,d). The PSCs have many similar features to hepatic stellate cells and the P2X7R may be an important target in combating pancreatic fibrosis and injury, similar to what has been seen with hepatic stellate cells in the liver [50,51].…”
Section: Discussionmentioning
confidence: 70%
“…In the present study, we confirm that the P2X7R stimulates collagen I secretion in vitro (Figure 3c,d). The PSCs have many similar features to hepatic stellate cells and the P2X7R may be an important target in combating pancreatic fibrosis and injury, similar to what has been seen with hepatic stellate cells in the liver [50,51].…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, our novel loci include genes that play roles in obesity (e.g., FTO, PPARG), insulin resistance (e.g., COBLL1, MIR5702 [IRS1]), and diabetes (e.g., HNF1A). Relevant for hepatic inflammation in the two-hit hypothesis of NAFLD 59 , our novel loci also implicate immunemediated or inflammatory contributions to NAFLD progression, including HLA, RORA 60,61 , IFI30 62,63 , CD276 64 , ILRN 62,65 , ITCH 66,67 and P2RX7 [68][69][70] . Among these, RORA encodes the retinoic acid receptor related orphan receptor A which may be involved in NASH pathogenesis through macrophage polarization and miRNA122, which comprises 70% of the total miRNA in liver 60,61 .…”
Section: Discussionmentioning
confidence: 74%
“…IFI30 encodes gamma-interferon-inducible lysosomal thiol reductase (GILT) which is involved in antigen processing and presentation and the production of reactive oxygen species during cellular stress and autophagy. Finally, P2RX7 encodes the purinergic receptor P2×7 which is involved in inflammasome activation and IL-1β processing in liver inflammation and fibrosis 68-70 . Encouragingly, these and additional pathways have emerged despite the proxy nature of our phenotype, and almost certainly underestimate the true number of loci contributing to NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader perspective, emerging evidence shows the involvement of the P2X7R-NLRP3 inflammasome pathway in the induction of non-alcoholic fatty liver disease (NAFLD) and liver fibrosis, suggesting possible therapeutic strategies targeting the P2X7 receptor/NLRP3 inflammasome [ 99 ]. In a CCL4-induced, nonhuman primate model of liver fibrosis, treatment with a P2RX7 inhibitor (SGM-1019) improved histological characteristics of non-alcoholic steatohepatitis (NASH), protecting from liver inflammation and fibrosis [ 100 ]. Furthermore, Tung et al (2015) found that a P2X7R blockade (using brilliant blue G and oxidized ATP) ameliorates liver fibrosis, mesenteric angiogenesis, and severity of portal-systemic shunting and improves the portal-systemic collateral vascular responsiveness in ATP in rats with bile duct ligation-induced cirrhosis, suggesting the potential of purinergic receptor antagonism in controlling liver cirrhosis-related complications [ 101 ].…”
Section: Conclusion and Therapeutic Perspectivesmentioning
confidence: 99%